Training and Developing Employees in the Industrial Revolution of 4.0 Era - Periasamy , Lalitha; Omar, Siti Sarah; Rashid, Umi Kartini; Bujang, Nazarudin (Research in Management of Technology and Business, 2020)
Industrial Revolution 4.0 known as smart factory, which can help industries to increase dominance and reliance on technology to produce far reaching efficiencies across a wide variety of sectors. Industry 4.0 can speed up innovation of a company, more flexible towards market changes and can speed up company growth. The objective of this study is to identify the nature of Industrial Revolution 4.0 and to the impacts of IR 4.0 towards employee training and development. In future this Industrial Revolution 4.0 will bring new categories of jobs, require new skill-sets and transform the way people work. This a review paper that employs secondary data analysis as the methodology. Related papers from years of 2015 and onwards are reviewed to identify the trend and practice used in training and developing employees for the Industrial revolution of 4.0 era. When an organization looking forward for their company growth, they need technology development at the same time workforce development to handle and understand the new technology which they plan to implement in their workplace. Companies are responsible to create intelligent workforce for their future.